Epidural Hydroxyethyl Starch in Treatment of Post Epidural Puncture Headache: A Case Series and Literature Reviews - Lai Y; Li W; Zhao D; Liang X; Fang J (International Medical Case Reports Journal)
Yucheng Lai,1 Wanhong Li,1 Dizhou Zhao,2 Xiaoyang Liang,1 Jieyu Fang1,3 1Department of Anesthesiology, Guangxi Hospital Division of the First Affiliated Hospital, Sun Yat-sen University, Nanning, Guangxi, People’s Republic of China; 2Department of Anesthesiology, Shenzhen People’s Hospital, The Second Clinical Medical College, Jinan University, The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, People’s Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Jieyu Fang, Email fangjy@mail.sysu.edu.cnBackground: Post-dural puncture headache (PDPH) is a common complication of obstetric anesthesia. There are still no convenient and effective methods to control the PDPH.Case Presentation: Three cases of parturients with accidental dural puncture who suffered post-dural puncture headache (PDPH) after labor analgesia or cesarean section. They were treated with epidural hydroxyethyl starch (HES) through an epidural catheter and achieved well therapeutic effect.Conclusion: Treatment of PDPH by epidural HES is a promising method that may benefit the parturient and doctor.Keywords: post-dural puncture headache, PDPH, hydroxyethyl starch, epidural pump, parturient